Sistem Uji Kualitas Air Kultur Daphnia Sp. menggunakan Logika Fuzzy berbasis NodeMCU - Fauzi Ali Farhi; Mochammad Hannats Hanafi Ichsan; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Daphnia are a good natural food source for freshwater fish larvae or fry. Daphnia sp. had a protein content ranging from 42-54%, a fat content ranging from 6.5-8% of dry weight, and linoleic and linolenic fatty acids ranging from 7.5 and 6.7%, respectively. Testing the quality of the water where Daphnia lives is something that needs to be considered so that the Daphnia product is good. Water quality parameters that need to be monitored are, for example, temperature and pH. Therefore, research is needed that can facilitate testing the quality of Daphnia culture water. Namely the Daphnia culture water quality test system. The method used is fuzzy sugeno to determine the value of water quality based on the parameter values given by the ds18b20 temperature sensor and 4502c ph sensor. The test produced by the ds18b20 temperature sensor has an average error value of 0.88%. by comparing 9 samples, three of cold water, three of normal water, and three of hot water, to a digital thermometer. For testing the ph sensor has an average error result of 9.5%. By testing using 5 different types of water, namely: well water, pond water, pH buffer 4 water, pH buffer 7 water, and pH buffer 9 water compared to digital pH. Testing the fuzzy method produces an average error value of 2,89%.